Integrasi Nilai Pancasila dalam Implementasi Syariat Islam di Aceh: Kajian Literatur terhadap Relasi Ideologi Negara dan Hukum Islam - Yalizar Rahayu Sitorus; Mina Umrah Pelas; Anggreni Bako; Abshari Abshari; Maulana Reyno Gunanza; Arfi Falaki Samba (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study examines the integration of Pancasila values in the implementation of Islamic Sharia in Aceh within the framework of Indonesia’s state ideology. The research employs a qualitative approach using a systematic literature review to analyze relevant academic sources, legal documents, and prior studies. Data were analyzed through thematic content analysis, involving processes of data reduction, categorization, and interpretative synthesis. The findings indicate that the implementation of Islamic Sharia in Aceh reflects a substantial alignment with the core principles of Pancasila, particularly in the domains of religious values, social justice, democratic deliberation, and national unity. This alignment is not merely normative but is operationalized through legal instruments such as qanun and institutional mechanisms supporting Sharia governance. However, the analysis also reveals underlying tensions, particularly in public perception and generational understanding, where Pancasila and Sharia are sometimes viewed as conflicting frameworks. This study contributes by providing a conceptual synthesis that positions the implementation of Sharia in Aceh as a contextual manifestation of Pancasila values, rather than a competing ideological system. The findings highlight the importance of strengthening integrative understanding between religious law and state ideology to ensure sustainable socio-legal harmony.